HUBUNGAN FREKUENSI MAKAN DAN POLA TIDUR DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI DI SMP NEGERI 2 LABUAPI TAHUN 2024 - ENDY BEBASARI ARDHANA PUTRI; ROSITA KHAERINA; FITRI DESTIANI (Universitas Mahasaraswati K. Mataram, 2024)
Adolescents are individuals within the age range of 10 to 18 years. Anemia is a common condition frequently observed during this stage of development. Several factors influence hemoglobin levels, including eating frequency and sleep patterns. This study aims to examine the relationship between eating frequency and sleep patterns with anemia on female adolescents at SMP Negeri 2 Labuapi in 2024. This study employs a quantitative research design with a cross-sectional approach. The population consists of female adolescents in grade VII at SMP Negeri 2 Labuapi. A purposive sampling technique was utilized, resulting in a sample size of 45 female adolescents. Data collection instruments included questionnaires and hemoglobin (HB) checkers. Data analysis was conducted using the chi-square test. The study results show that 30 respondents (66.7%) have good eating frequency, while 15 respondents frequency. Additionally, 27 respondents (33.3%) have poor eating (60%) exhibit poor sleep patterns, and 18 respondents (40%) have good sleep patterns. Anemia is present in 27 respondents (60%), while 18 respondents (40%) are not anemic. The analysis reveals the relationship between eating frequency and anemia is p 0.519, meanwhile, the relationship between sleep patterns and anemia is p = 0.000. In conclusion, there is no relationship between eating frequency and anemia among female adolescents at SMP Negeri 2 Labuapi in 2024. However, a relationship is found between sleep patterns and anemia in this population.